The Influence of Health Facilities Information System Application in The Business Process of Clinic Bunga Melati - Geby Firdana Puspa; Raden Venantius Hari Ginardi (IPTEK Journal of Proceedings Series, 2020)
In this competitive business era, Klinik Bunga Melati (KBM) has changed its business and management strategies 3 times in the last 2 years with the aim of adjusting internal and external conditions in the health sector and make KBM superior to other competitors. KBM expects the development of technology that can be applied efficiently and integrated between KBM internally. In 2018, KBM teamed up with the Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan. In this regard, BPJS provides a Health Facilities Information System (HFIS) with the aim of making it easier for health units to make claims. But the leader of the KBM considers HFIS not suitable to be implemented in the KBM Welirang Branch. The KBM Welirang Branch staff must do 2x recapitulation of patient medical records every day. There are quite a lot of variables in HFIS besides self-data, staff must also write data related to diagnosis, details of drugs used, drug costs, and doctor's fees. Based on the KBM leaders interview, this is considered to be very time-consuming and costly because HR has to work 2x more and patients need more time to get action. HOT-Fit method is considered suitable for this research because this model can provide an explanation and provide an evaluation of the application a system in the field of health services from human factors (human), technology (technology), organization (organization) and net benefits. The output of this research is an analysis of aspects that need to be improved and the match rate of HFIS implementation in the KBM Welirang.